School and Work : Does the Eastern Caribbean Education System Adequately Prepare Youth for the Global Economy? - Blom, Andreas; Hobbs, Cynthia (World Bank, Washington, DC, 2012)
As the global economy rapidly changes and new technologies are introduced, more highly skilled workers are required. In the Organization of Eastern Caribbean States (OECS), firms struggle to fill skilled positions due to a lack of qualified candidates, while the number of unemployed low skilled workers is growing. This report is organized into six chapters. After on introduction, the second chapter makes the argument for why skills matter to the OECS countries. The subsequent three chapters emphasize how education (school) is intrinsically linked to the labor market, both in providing initial preparation and training and in updating workers' skills throughout adulthood (lifelong learning). Thus, the third chapter discusses how adequately the schools in the OECS prepare youth for the labor market. The fourth chapter focuses on the transition from the education system to the labor market. The fifth chapter analyzes the opportunities for workers to continue learning while in the labor force. The final chapter summarizes the main policy recommendations for improving education and training in the OECS. Transversal themes run through the report: (i) deepening sub-regional collaboration; (ii) increasing involvement of the private sector in education and training; (iii) enhancing collaboration across different levels of the education and training systems; (iv) improve the quality and relevance of education will better prepare youth for the labor market; and (v) improve the quality of education.